COMPLICATIONS AND TREATMENT OBSERVED IN THE PATHOLOGY OF THE ADENOID GLAND IN CHILDREN WHO PRONE TO THE DISEASE - Husanov Shoyatbek Rustamjonovich (Web of Journals Publishing, 2024)
In this case, the annotation summarizes the article "Complications and Treatment of Adenoid Hypertrophy in Children." It highlights the prevalence of adenoid hypertrophy in children, its associated complications such as nasal obstruction and sleep apnea, and various treatment options including watchful waiting and adenoidectomy. The annotation also underscores the importance of early detection, comprehensive care, and collaboration among healthcare professionals and caregivers in managing adenoid hypertrophy effectively.
Keywords: Complications, Treatment. Nasal obstruction, Obstructive sleep apnea, Recurrent ear infections, Sinusitis, Adenoidectomy, Multidisciplinary approach.